The perception of stakeholders towards the viability of takaful in India - Salman, Syed Ahmed (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
Insurance is a well-known mechanism for risk management in India, and it has been in existence since 1818. It is undeniable that insurance is helpful to the policyholders because if misfortune inflicts them, insurance can provide the financial assistance according to the terms and conditions of the policy. However, the main drawback of the conventional insurance scheme is that its practices are prohibited from the Islamic perspective. Many Muslim and non-Muslims countries have introduced the Takaful as an alternative to insurance. However, India as the second largest Muslim populated country has no experience with Takaful. This encourages the researcher to identify why Takaful has not been introduced in India. The main objective of this study is to examine the perception and acceptability of insurance policyholders, insurance operators, Islamic finance experts and politicians to introducing Takaful in India. Primary data is collected by distributing a survey questionnaire to the insurance policyholders and conducting interviews with insurance operators, Islamic finance experts and politicians. The main theories used are the new product adoption theory and the new product diffusion theory to develop five hypotheses. A few sampling techniques under the non-probability sampling method, such as the snowball sampling for the policyholders and expert sampling or judgmental sampling method for insurance operators, Islamic finance experts and politicians are used. Based on the analysis of the survey questionnaire from the insurance policyholders, the findings are in line with four alternative hypotheses and not in line with the last alternative hypothesis. Firstly, there is a positive relationship between participating (adopting) in Takaful products and the awareness of prohibition of conventional insurance from the religious aspects. Secondly, there is also a positive relationship between participating (adopting) in Takaful products and the level of knowledge on Takaful products. Thirdly, there is a positive relationship between participating (adopting) in Takaful products and internal forces (determinants). Fourthly, there is a positive relationship between participating (adopting) in Takaful products and external forces (determinants) on the customers. The last alternative hypothesis, i.e. there is no significant difference between Muslims and non-Muslims in terms of participating (adopting) of Takaful products, is not supported. The main findings from the interviews are that it is viable to introduce Takaful in the near future although some obstacles and challenges might hinder its introduction. Insurance operators highlight the strengths, weaknesses, opportunities and threats of introducing Takaful. Islamic finance experts suggest using a hybrid Mudarabah-Wakalah model for both general and family Takaful products. Politicians seem to support it as long as the Takaful scheme can contribute to the economic development of the country and serve the needs of the community. This research offers a comprehensive study on the viability of Takaful in India, and hence, it will be of interest to operators, investors, regulators as well as the current and potential participants.